Strategies used by peer-facilitators to promote reflective learning amongst the first-year students: a case study of one university in South Africa - Baleniand, Lulekwa Sweet-Lily; Adu, Emmanuel Olusola (Penerbit Universiti Kebangsaan Malaysia, 2020)
The views of peer facilitators on the strategies used to promote reflective learning on the first-year students were explored in this study. Purposive sampling was used to select the participants, which is a qualitative inquiry situated in the interpretive paradigm. The researcher also used in-depth interviews to collect data and analysed data using the thematic analysis. The study found that the peer facilitators used group work, group discussion, spider diagrams and limited technology. However, it emerged that besides the limited technological strategies crippled by the disenabling conditions within the institution, the lack of support from both students and lecturers is a demotivating factor for some of these peer facilitators and thus this affects their efforts to assist students. The paper recommends the implementation of the multi-sectoral approach, training and continuous professional development of peer facilitators on reflective practices using both conventional methods and digital technologies, the inclusion of reflective learning in the facilitation methods within the module learning guides/ course outlines to promote reflective learning.